Collaborative Problem-Solving Phase in Mathematics: A Case Study in Geometric Problem-Solving - Arif Hidayatul Khusna; Alfiani Athma Putri Rosyadi; Minatun Nadlifah (AT-TA'LIM, 2024)
Problem-solving is an activity that can support knowledge construction. Polya, Mason, and Schoenfeld see the problem-solving process as an activity carried out in an individual context. A person's activities cannot be separated from individual interactions. Collaborative Problem-Solving (CPS) is a situation where students must use problem-solving and communication skills in group work to solve a problem. This research examines the stages of collaborative problem-solving in case studies of geometric problem-solving. This research is a case study type with a qualitative approach. The research subjects were class X high school students. The research instruments used were collaborative plane geometry problem-solving questions and interview guidelines. The data collection method was carried out by providing collaborative problem-solving tasks and interviews. The recording was carried out during the assignment using an audio recorder to see the collaborative mathematical problem-solving phase. The research results show that problem-solving starts with discussing, conjecturing, building solutions, communicating reasoning, and extending. The problem-solving phase is cyclical at certain stages, namely discuss – conjecture – build solution – discuss. Meanwhile, critique merges the discussion, conjecture, solution-building, and communication reasoning stages. The finding of the CPS phase in this research is that it has cyclical stages. It combines the critique stages in each CPS phase and can be considered if different CPS phases are documented. Apart from that, it can be a consideration for students that the problem-solving stages in collaboration are more flexible.